Further validations of the hydrodynamic force coefficients for a laterally drifting ship in waves - Baharudin, Bakhtiar Ariff (2009)
Lateral drift effects are caused by the effects of wind forces and /or wave drifting forces acting on ships in actual seas Lateral drift effect has been found to have significant effects in the ship motion.(Faizul A. A. 2006). . The lateral drift effect are one of the effects that is included in the ship motion prediction to determine a good seakeeping performance of the ship.Another approach to determine the effects of lateral drift has been done in this project. The approach is by taking several sets of offset data at different drift angle. The new approach is named The Alternative Strip Method (ASM). The ASM will be another method to calculate the effects of lateral drift on the ship motion prediction. From the results obtained from the ASM calculations, the lateral drift effects are further verified on 2D/3D hydrodynamic force coefficients on floating body and 3D ship.